2016
DOI: 10.1063/1.4958618
|View full text |Cite
|
Sign up to set email alerts
|

Leakage and field emission in side-gate graphene field effect transistors

Abstract: We fabricate planar graphene field-effect transistors with self-aligned side-gate at 100 nm from the 500 nm wide graphene conductive channel, using a single lithographic step. We demonstrate side-gating below 1 V with conductance modulation of 35% and transconductance up to 0.5 mS/mm at 10 mV drain bias. We measure the planar leakage along the SiO2/vacuum gate dielectric over a wide voltage range, reporting rapidly growing current above 15 V. We unveil the microscopic mechanisms driving the leakage, as Frenkel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
54
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

7
3

Authors

Journals

citations
Cited by 90 publications
(60 citation statements)
references
References 46 publications
5
54
0
1
Order By: Relevance
“…Such high value is in agreement with other reports on similar devices [41]. The 11 noise equivalent power (NEP), which represents the minimum detectable optical power, defined as the rms optical power required to produce a signal-to-noise ratio of 1 in a 1 Hz bandwidth, is less than 0.1 Wcm −2 . Since the signal increases linearly with the area, while the noise varies as the square root of the area of the photodiode [38], the detectivity…”
Section: Resultssupporting
confidence: 92%
“…Such high value is in agreement with other reports on similar devices [41]. The 11 noise equivalent power (NEP), which represents the minimum detectable optical power, defined as the rms optical power required to produce a signal-to-noise ratio of 1 in a 1 Hz bandwidth, is less than 0.1 Wcm −2 . Since the signal increases linearly with the area, while the noise varies as the square root of the area of the photodiode [38], the detectivity…”
Section: Resultssupporting
confidence: 92%
“…It has been observed that a PMMA film, or even only residues of it, cause p-type doping of graphene and other 2D channels due to the presence of oxygen. The p-type conduction is either explained considering the charge transfer to oxygen which, acting as electron capture center, suppresses the free electron density, or ascribed to the pinning of the Fermi level close to the maximum of the valence band, which favors the hole conduction [27,[37][38][39]. Here, we report a similar effect for WSe FETs.…”
Section: Resultssupporting
confidence: 56%
“…[], have been reported and GNR MOSFETs capable of modulating the drain current over several orders of magnitude by varying the gate voltage have been demonstrated . Moreover, well‐behaving GNR side‐gate transistors and GNR TTJ (three terminal junction) devices showing voltage rectification have been reported.…”
Section: Introductionmentioning
confidence: 99%